2014
DOI: 10.9790/2402-08720513
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Airport’s Environmental Issues (Case Sam Ratulangi International Airport of Manado)

Abstract: This study aims to map the environmental issues that occurred at the Sam Ratulangi International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…These levels were also greater than the recommended benchmark. The noise investigation that was conducted in Poland and Columbia demonstrates that the equivalent level of noise remains within the prescribed value (Sondakh et al, 2014). The process of industrialization goes hand in hand with the progress made by develop-ing countries.…”
Section: Previous International Study On Noise Monitoring and Mappingmentioning
confidence: 97%
“…These levels were also greater than the recommended benchmark. The noise investigation that was conducted in Poland and Columbia demonstrates that the equivalent level of noise remains within the prescribed value (Sondakh et al, 2014). The process of industrialization goes hand in hand with the progress made by develop-ing countries.…”
Section: Previous International Study On Noise Monitoring and Mappingmentioning
confidence: 97%
“…The study also found that annoyance had an effect on health but there was no evidence of its long-term effect on general health. 16 Relatedly & Sondakh et al, 2 in measuring and evaluating noise levels arising from the operation of Saniratulangi International Airport on the surrounding environment used Standard measurement using sound level meter (SLM) and perception of the people who lived around the airports using a Questionnaire. They employed survey, observation, and documentation in order to obtain the data and information required.…”
Section: Negative Impact Of Airportmentioning
confidence: 99%
“…Related researches have been carried out in different parts of the world on airports to assess the health implication of airport noise on host communities. [2][3][4][5] However; it would seem that since the Ibom international Airport is a recent development, little or no research has been carried out on the airport. This has necessitated this research, to assess the socio-economic impact of the airport on host communities.…”
Section: Introductionmentioning
confidence: 99%
“…Some cases related to environmental pollution include toxic waste from the inflight catering service ACS, a subsidiary of the Indonesian aviation company PT Angkasa Pura in 2016 (e.g. Sondakh, et al, 2014). Pollution done by M SM Es is not less worrying (e.g.…”
Section: Introductionmentioning
confidence: 99%